Physical predictors for moderate to severe obstructive sleep apnea in snoring patients - Banhiran, Wish; Junlapan, Attapon; Assanasen, Paraya; Chongkolwatana, Cheerasook (Sleep & breathing, 2014)
Purpose This study aimed to identify physical findings that may predict the presence of moderate to severe obstructive sleep apnea (OSA) in snoring patients. Methods A total of 283 subjects (165 males and 118 females) were recruited, including 217 OSA patients and 66 patients with apnea–hypopnea index (AHI) < 5 as a control group, diagnosed by level-1 polysomnography. Baseline data of patients including age, sex, weight, height, body mass index (BMI), neck circumference (NC), waist circumference (WC), neck-to-height ratio (NHtR), and waist-to-height ratio (WHtR) were recorded. Other physical parameters such as chin length (Chin1), thyromental distance, hyomental distance, cricomental distance, cricomental space (CMS), Friedman tongue position (FTP), and tonsils size were recorded by a single investigator who was blinded to the PSG results. Results The findings that were statistically different between the control group and moderate to severe OSA (AHI ≥ 15) included sex, BMI, NC, NHtR, WC, WHtR, Chin1, CM, and CMS ( p < 0.05). However, logistic regression analysis showed that only male gender and WHtR ≥ 0.55 were the independent predictors for AHI ≥ 15 with adjusted odds ratios of 6.6 and 3.1, respectively. Conclusion Among snoring patients seeking medical consultation, male gender and WHtR of ≥ 0.55 were good predictors for moderate to severe OSA. No single head and neck finding reliably predicted this condition. In a situation with limited facilities, these data along with medical history may be helpful for prioritizing patients in order to achieve the optimal use of sleep investigation and treatment.